Influence of the Cathode Potential on Electrode Interactions within a Li4Ti5O12 vs LiNi3/5Mn1/5Co1/5O2 Li-Ion Battery. Issue 4 (11th February 2020) - Gauthier, Nicolas; Courrèges, Cécile; Demeaux, Julien; Tessier, Cécile; Martinez, Hervé
Abstract : Interactions occurring between positive and negative electrodes and their impact on electrode–electrolyte interfaces during constant current cycling in LiNi3/5 Mn1/5 Co1/5 O2 //Li4 Ti5 O12 li-ion batteries are investigated at various upper cutoff voltages by performing XPS and ToF-SIMS analysis. Below 4.3 V (potential of NMC electrode vs Li 0 /Li + ), good capacity retention and low impedance increase over cycles are obtained whereas at higher cycling positive electrode potential, serious capacity loss and critical increase of electrochemical impedance are observed due to electrolyte degradation at the Ni-rich NMC electrodes. This study highlights that salt (LiF and fluorophosphates) and solvents (–CO containing species) degradation products and NMC dissolution products such as manganese or nickel species are formed at the NMC electrodes then migrate to the LTO electrodes surface in full-cells, and these phenomena are intensified at high voltage. Moreover, the formation and the deposition of organo-fluoro-phosphates in the outer part of the SEI of LTO electrodes is revealed thanks to ToF-SIMS molecular in-depth analysis. These results provide valuable insights on the behavior of interfaces at LTO electrodes upon cycling vs NMC at high potential. Overall, failure mechanisms are driven by oxidative parasitic reactions at the cathode and interactions with the anode.